ETS-Related Gene Expression in Healthy Femoral Arteries With Focal Calcifications - Vasuri, Francesco; Valente, Sabrina; Motta, Ilenia; Degiovanni, Alessio; Ciavarella, Carmen; Pasquinelli, Gianandrea (Frontiers in Cell and Developmental Biology, 2021)
Bone development-related genes are enriched in healthy femoral arteries, which are more prone to calcification, as documented by the predominance of fibro-calcific plaques at the femoral location. We undertook a prospective histological study on the presence of calcifications in normal femoral arteries collected from donors. Since endothelial-to-mesenchymal transition (EndMT) participates in vascular remodeling, immunohistochemical (IHC) and molecular markers of EndMT and chondro-osteogenic differentiation were assessed. Transmission electron microscopy (TEM) was used to describe calcification at its inception. 214 femoral arteries were enrolled. The mean age of donors was 39.9±12.9 years; male gender prevailed (M: 128). Histology showed a normal architecture; calcifications were found in 52 (24.3%) cases, without correlations with cardiovascular risk factors. Calcifications were seen on or just beneath the inner elastic lamina (IEL). At IHC, SLUG was increasingly expressed in the wall of focally calcified femoral arteries (FCFA). ERG, SLUG, CD44, and SOX-9 were positive in calcifications. RT-PCR showed increased levels of BPM-2, RUNX-2, alkaline phosphatase and osteocalcin osteogenic transcripts and increased expression of the chondrogenic marker, SOX-9, in FCFA. TEM documented osteoblast-like cells adjacent to the IEL, releasing calcifying vesicles from the cell membrane. The vesicles were embedded in a proteoglycan-rich matrix and were entrapped in IEL fenestrations. In this study, ERG and CD44 positive cell populations were found in a context of increased SLUG expression, thus supporting the participation of EndMT in FCFA; the increased transcript expression of osteo-chondrogenic markers, particularly SOX-9, reinforced the view that EndMT, osteo-chondrogenesis, and neoangiogenesis interact in the process of arterial calcification. Given its role as a transcription factor in the regulation of endothelial homeostasis, arterial ERG expression can be a clue of endothelial dysregulation and changes in IEL organization which can ultimately hinder calcifying vesicle diffusion through IEL fenestrae. These results may have a broader implication for understanding arterial calcification within a disease context.